2017
DOI: 10.4103/ijccm.ijccm_2_17
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory multiplex polymerase chain reaction: An important diagnostic tool in immunocompromised patients

Abstract: Background:Viruses and atypical pathogens can cause significant respiratory illness in immunocompromised patients. Multiplex polymerase chain reaction (MPCR) has improved the diagnostic yield of pathogens, and it is easier to identify the co-infections also. The present study was done to evaluate the performance of MPCR on bronchoalveolar lavage (BAL) samples in immunocompromised patients.Methods:Atotal of 177 BAL specimens collected over a 19 months period from immunocompromised patients with respiratory illn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…sensitivity by also detecting genotypic markers of resistance. Multiple studies have demonstrated the superior diagnostic accuracy of PCR based platforms for detecting bacterial pathogens in the sputum compared with standard culture [16][17][18][19] . This review will discuss the commercially available syndromic molecular panels for pneumonia, their potential clinical impact and the challenges to implementing them as a 'front line' diagnostic test.…”
Section: Introductionmentioning
confidence: 99%
“…sensitivity by also detecting genotypic markers of resistance. Multiple studies have demonstrated the superior diagnostic accuracy of PCR based platforms for detecting bacterial pathogens in the sputum compared with standard culture [16][17][18][19] . This review will discuss the commercially available syndromic molecular panels for pneumonia, their potential clinical impact and the challenges to implementing them as a 'front line' diagnostic test.…”
Section: Introductionmentioning
confidence: 99%